Organizational fairness and task performance: a study between different activities and positions in the justice sector - Santos, Edicreia Andrade dos; Venturini, Lauren Dal Bem; Sallaberry, Jonatas Dutra; Klein, Luciana; Flach, Leonardo (Revista de Administração da UFSM, 2023)
Purpose: This study analyzes the effects of organizational justice on the performance of tasks in the justice sector, divided by activity and position. Design/methodology/approach: We applied structural equations to a sample of 474 employees of the Public Prosecutor. Findings: A direct and positive effect of distributive justice and interactional justice on task performance was discovered. However, aspects of procedural justice do not have a significant relationship with task performance. The performance of non-core activities is positively influenced by interactional justice and the final activity by distributive justice. As for the positions, the interactional dimension has a significant magnitude in the position of analyst, while the distributive and procedural justice affect the performance of the technician's positions. Practical implications: These findings provide an understanding of how organizations can build their organizational structure between middle and end activities, to increase the perception of justice of their servers, and consequently improving the performance of activities. Originality: The article explores in an unprecedented way the perception of organizational justice in different work functions - the core activity and the non-core activity.